A synchronous generator circuital model for internal fault analysis and protection system design. (21st February 2013) - Delfino, F.; Denegri, G. B.; Invernizzi, M.; Pampararo, F.; Procopio, R.
SUMMARY: This paper presents a model for the analysis of internal faults of synchronous generators with multiple parallel connection paths for phase. Several kinds of faults between different portions of the stator windings (and ground, if the case) can be described in the subtransient time frame. Data necessary for the model derive from the electromagnetic design of the machine, as well as from details on equivalent parameters of the external grid and from the neutral connection characteristics. Such modeling procedure allows accurate insight of currents in windings and terminals, exploring each possible fault configuration. In the second part of this work, the developed model will be applied to assess the validity and to define possible improvements of conventional protection configurations against internal faults. Copyright © 2013 John Wiley & Sons, Ltd.